PEMBELAJARAN MENGIDENTIFIKASI TEKS LAPORAN HASIL OBSERVASI YANG DIPRESENTASIKAN SECARA LISAN DAN TULISAN DENGAN TEKNIK IDENTITAS KORPORAT PADA SISWA KELAS X SMK ANUGERAH TONDANO - Yuwenda Tabuni; Intama J Polii; Oldie S Meruntu (KOMPETENSI, 2022)
This study aims at 1) Describing the learning process of identifying written observation report text by using corporate identity technique to the 10th Grade Students at SMK Anugerah Tondano, and 2) Describing 10th Grade students’ ability to identify written observation report text using corporate identity technique at SMK Anugerah Tondano. The research method used in this study is descriptive analytic method. 17 10th grade students at SMK Anugerah Tondano are the source of the data. Observation and test are used to collect the data for this study. The study finds that the use of indentity corporate technique improves learning process quality and students’ learning outcome. This technique also helps the teacher to foster students’ motivation and engagement in learning activity. Students’ ability to identify written observation report text is reflected in the following aspects: 1) Identifying general questions on the text (86,75%), 2) Writing down 5 important information on the text (87,63%), 3) Writing down the description of parts on the text (87,23%), and 4) Writing down the description of benefits on the text (82,05%). The average score of the students’ ability in identifying written observation report text is 85,94%, which means they are categorized as competent.